Characterization of Conjugated Polymer Poly(fluorene-co-thiophene) and Its Application as Photosensitizer of TiO2 - Rongliang Qiu; Lin Song; Dongdong Zhang; Yueqi Mo; Eric Brewer; Xiongfei Huang (International Journal of Photoenergy)
The copolymer poly(fluorene-co-thiophene) (PFT) has strong absorption in the visible light region. In this paper, PFTs with four different thiophene contents were evaluated for their suitability as photosensitizers of TiO2. All four of the PFTs were capable of being excited by light with wavelengths above 455 nm, and all had reductive potentials more negative than the conduction band potential of TiO2. Consequently, it was deemed that transfer of electrons from the excited PFTs to the conduction band of TiO2 was thermodynamically possible. PFTs with higher thiophene content had more electron transitions in the excited state, resulting in increased photocatalytic activity of PFT-sensitized TiO2. The method used to prepare the combined PFT/TiO2 photocatalyst affected its photocatalytic activity. Best results in this study were achieved by dropwise addition of a tetrahydrofuran solution of PFT to a stirred TiO2/ethanol suspension.